Effect of recovery method and oxygen tension on development of bovine oocytes fertilized and cultured in vitro - Benavides I., Lenin (2015)
The aim of this study was to evaluate the effect of the recovery method and oxygen tension on in vitro embryo (IVP) production. In Experiment 1 the effect of two recovery methods, aspiration and dissection on embryo division and development rates was evaluated. The 72 hour post-insemination division rate was 71.4% with aspiration and 61.0% with dissection (p<00.5), while no statistical difference was found on blastocyst rates 7 and 9 days post-insemination. In Experiment 2 two oxygen tensions, 5 and 20%, were compared in the culture stage obtaining higher division rate and 7-day blastocyst rate with 5% oxygen tension (69.7 and 29.8% respectively) compared with 20% oxygen tension (59.7 and 19.3% respectively). The results suggest that the aspiration recovery method and 5% oxygen tension must be considered to achieve optimal conditions for in vitro embryo production.